Development of Phonological Constancy: 19‐Month‐Olds, but Not 15‐Month‐Olds, Identify Words in a Non‐Native Regional Accent. Issue 6 (22nd March 2013) - Mulak, Karen E.; Best, Catherine T.; Tyler, Michael D.; Kitamura, Christine; Irwin, Julia R.
Abstract : By 12 months, children grasp that a phonetic change to a word can change its identity ( phonological distinctiveness ). However, they must also grasp that some phonetic changes do not ( phonological constancy ). To test development of phonological constancy, sixteen 15‐month‐olds and sixteen 19‐month‐olds completed an eye‐tracking task that tracked their gaze to named versus unnamed images for familiar words spoken in their native (Australian) and an unfamiliar non‐native (Jamaican) regional accent of English. Both groups looked longer at named than unnamed images for Australian pronunciations, but only 19‐month‐olds did so for Jamaican pronunciations, indicating that phonological constancy emerges by 19 months. Vocabulary size predicted 15‐month‐olds' identifications for the Jamaican pronunciations, suggesting vocabulary growth is a viable predictor for phonological constancy development.